EFEKTIVITAS PENGGUNAAN MULTIPLE MICRONUTRIENTS (MMN) TERHADAP JUMLAH PERSALINAN NORMAL DAN SESAR - Najmiatul Fitria; Sarah Puti Amalia; Nauratul Ikramah; Hansen Nasif (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Health problems during pregnancy drop the number of normal deliveries in pregnant women. The World Health Organization recommends pregnant women consume folic acid, iron, and multiple micronutrients. This study aims to determine the effectiveness of using Multiple Micronutrients (MMN) on delivery forms. This research was conducted at Semen Padang Hospital, Padang. This study is a descriptive study with data collection carried out retrospectively. The sample in this study was data from pregnant women who did prenatal care and gave birth at Semen Padang Hospital in January-December 2021. The number of samples in this study was 201 pregnant women, divided into 73 pregnant women with normal deliveries and 128 patients with normal deliveries by cesarean section. In this study, the value of p = 0.767 (p>0.05) with the interpretation of the effectiveness of the use of IFA was not different from the effectiveness of MMN in the number of normal deliveries